Crystal structure of 3,5-bis(trifluoromethyl)benzyl(Z)-N-(adamantan-1-yl)morpholine-4-carbothioimidate, C24H28F6N2OS - Al-Wahaibi Lamya H.; Hassan Hanan M.; Ghabbour Hazem A.; El-Emam Ali A. (Zeitschrift für Kristallographie - New Crystal Structures, 2018)
C24H28F6N2OS, monoclinic, P21/n (no. 14), a = 17.4112(7) Å, b = 8.3694(3) Å, c = 17.6728(7) Å, β = 104.612(2)°, V = 2492.01(17) Å3, Z = 4, Rgt(F) = 0.0603, wR(F2) = 0.1704, T = 293(2) K.